A STUDY OF SOCIAL LIFE, HEALTH AND NUTRITION OF TRIBALS IN NANDURBAR DISTRICT OF MAHARASHTRA (International Journal of Food and Nutritional Sciences, 2022)
Tribal tribes live in different regions of India. The state of Maharashtra also has a large tribal population and Nandurbar district in the state is known as a tribal district. Like other tribals of the country, tribals of this district have traditions. Adivasis are innocent people who live close to nature and consider nature as God. Their culture is equally natural in nature. Living in close proximity to nature, the social, cultural and economic life of these tribals is innocent and has no trace of selfishness. Although the life of the tribals is happy with such innocent companionship, they are not much attracted to modern medical facilities